Validação de um método cromatográfico – Microextração em fase sólida (CG-MEFS) para determinação de n- alcanos em água de produção. - Nobre, Crisiana de Andrade (2015)
The exploration and production of oil and gas generate waste and effluent, among which stands out the Produced water our oil production water. What this effluent is disposed on the Brazilian coast, around have 17x103 µg L-1hydrocarbon, that many times are persistent organic pollutants harming marine life. Among those hydrocarbons are the n-alkanes that are the main fuels in the production of derivatives several of the petrochemical industry. In this work and was validated um method for a determination of n-alkanes (C8 -C20) water in oil production. The gas chromatography coupled to flame ionization detector it used was as a tool for determination and quantification of these compounds. The factorial design realized for solid phase micro extraction (SPME) Indicated que leader board achieved are in central point region when using a temperature of 45 ° C and salinity of 7.5% w/ v. The method validation figures of merit indicate linearity, precision and accuracy satisfactory for all compounds studied. The values of correlation coefficients ranged between 0.9916 0.9999. The limits of detection (LOD) varied between 0.0029 and 0.0767 µg L-1 and the limits of quantification (LOQ) ranged between 0.0089 and 0.2326 µg L-1. Due to the significance Effect matrix for all compounds, the method of addition of standard applied for was quantification of analytes. The validated method applied was in the analysis of oil production water. Compounds C10 and C12, they were detected in a concentration maximum 13.17 and 8.34 µg L-1, respectively.